How to manage managers a workbook for middle managers - Franzén, Härje 1941-; Hardaker, Maurice 1931- (McGraw-Hill, 1994)
Being a middle manager is a unique job, but too often the assumption is made that if you are a first-line manager and are promoted you just carry on managing in the same way. Being a manager of managers requires new skills, yet there is little practical guidance available to middle managers to help them adapt and grow with this ever-changing and demanding role. This text concentrates on these essential and specific skills in a direct, practical and accessible way. It contains exercises and checklists which makes it easy to reference and adapt to the individual reader's requirements.